The Marriage à la Mode: Hospitality Industry’s Connection to the Dating Services Industry - Seraphin, Hugues; Yallop, Anca (School of Hospitality & Tourism, Auckland University of Technology, 2023)
The dating services industry has grown strongly over the past five years worldwide, with dating services increasing in popularity, contributing billions to the hospitality industry. In this opinion paper we carry out a preliminary examination of the connection between the dating industry and the hospitality industry and conduct a a pilot study as platform for further research seeking to examine the connections between these industries. The preliminary findings indicate that the dating services industry and the hospitality industry are interconnected, and that entertainment, service interaction and the hospitality venue’s ambiance are central factors to both the dating and hospitality industries. Nevertheless, future research must investigate further intersectional gaps, more specifically, to examine the synergies between business partners delivering products and services which are placed at this intersection between dating and hospitality.